Expression of Osteopontin and Cyclooxygenase-2 in relation to cellular proliferation, in non-tumor colonic mucosa, colonic adenomas and colon adenocarcinoma (2021)
Revista Ciencias Biomédicas Vol.10, Núm.1 (2021) Pag. 3 - 15